Penyelesaian Sengketa Pajak - Pamungkas, Hanggoro (Binus Business Review, 2011)
Indonesia has âself assessmentâ tax system to fulfill taxpayer obligation in complying Tax Laws and Regulations. In fact tax administration could occasionally make tax audit resulting a different assessmentand therefore taxpayers still have to pay. Any tax dispute of the tax administrations assessment will be reviewed by filling complain, and later any further tax assessments dispute will be solved by bringing the case by appealing to Tax Court. Study uses field data and other related readings,in field research is collecting related data including appeal letter and the Tax courts process, as well as library research collecting related data to support the analysis. Result of the research on three tax payers shows caused by some taxs or fiscals corrections, and in the tax court is neither not supported with reliable evidences, nor tax payers do not completely fulfill tax laws and regulations. The study on the cases suggesting that taxpayers have always to provide all related documents to make tax audits done accordingly, and tax payers could explain them to judges, andsuggestions for tax court could possibly to complete the review in six moths or sooner to avoid unnecessary additional cost to taxpayers on penalty.